031 The reduced benefit of sleep for memory trace consolidation with age. (3rd May 2021) - Toor, Balmeet; van den Berg, Nicholas; Ray, Laura; Fang, Lydia; Fogel, Stuart
Abstract: Introduction: Sleep is known to enhance the realization of novel solutions to problems. As we age, both the quantity and quality of sleep are reduced. Age-related deficits in sleep-dependent memory consolidation have been recently identified, however, the scope of these deficits is not. Here, we sought to investigate the behavioural and neuronal functional consequences of age-related changes in sleep for gaining insight into novel cognitive strategies (e.g., on the Tower of Hanoi; ToH). Methods: 40 healthy young adults (20–25 years), and 30 healthy older adults (60–85 years) participated, and were assigned to either the nap [young-nap (YN), older-nap (ON)] or wake [young-no-nap (YNN), older-no-nap (ONN)] conditions. Participants were trained on the ToH in the AM, followed by either a 90 minute nap opportunity or a period of wake, and were retested afterward. The ToH is a procedural task that requires the acquisition of a novel cognitive strategy (i.e., recursive logic). Alternating blocks of ToH practice and rest were performed while functional MRI scans were obtained at 3T to examine differences (pFDR<0.05) in brain activation from training to retest in young vs. older groups as a function of sleep [(YN-YNN)-(ON-ONN)]. Results: Sleep significantly benefitted the young but not the older participants (speed and accuracy) on the ToH. A bilateral difference in activation of the hippocampus was observed from training to retest between young and older subjects. Specifically, YN displayed decreased activation, whereas YNN showed increased activation. The older groups showed the opposite pattern whereby ON displayed increased activation whereas ONN showed decreased activation. The same pattern was observed for the middle temporal gyrus and medial prefrontal cortex. By contrast, the opposite pattern was observed in the premotor area, inferior and superior parietal cortex. Conclusion: These results suggest that sleep differentially contributes to the realization of a novel cognitive strategy in young vs. older individuals, consistent with the notion that as the consolidation of a newly formed memory trace progresses, the hippocampus becomes less involved over time; especially so when sleep occurs during that time. Our results suggest that sleep preferentially contributes to this process in the young, but not in older individuals. Support (if any):